Short and medium range structures of 80GeSe2–20Ga2Se3 chalcogenide glasses. (13th April 2018) - Petracovschi, Elena; Calvez, Laurent; Cormier, Laurent; Coq, David Le; Du, Jincheng
Abstract: The short and medium range structures of 80GeSe2 –20Ga2 Se3 (or Ge23.5 Ga11.8 Se64.7 ) chalcogenide glasses have been studied by combining ab initio molecular dynamics (AIMD) simulations and experimental neutron diffraction studies. The structure factor and total correlation function were calculated from glass structures generated from AIMD simulations and compared with neutron diffraction experiments showing reasonable agreement. The atomic structures of ternary chalcogenide glasses were analyzed in detail, and it was found that gallium atoms are four-fold coordinated by selenium (Se) and form [GaSe4 ] tetrahedra. Germanium atoms on average also have four-fold coordination, among which Se is 3.5 with the remaining being Ge–Ge homo-nuclear bonds. Ga and Ge tetrahedra link together mainly through corner-sharing and some edge-sharing of Se. No homo-nuclear bonds were observed among Ga atoms or between Ge and Ga. In addition, Se–Se homo-nuclear bonds and Se chains with various lengths were observed. A small fraction of Se atom triclusters that bond to three cations of Ge and Ga were also observed, confirming earlier proposals from 77 Se solid state nuclear magnetic resonance studies. Furthermore, the electronic structures of ternary chalcogenide glasses were studied in terms of atomic charge and electronic density of states in order to gain insights into the chemical bonding and electronic properties, as well as to provide an explanation of the observed atomic structures in these ternary chalcogenide glasses.